Effect of multiphase structure of plasma coatings on their elastic and strength properties - Kopylov, Viacheslav (Eastern-European Journal of Enterprise Technologies, 2016)
We examined physical and mechanical characteristics of multiphase plasma coatings of lamellar structure, which include nanocomponents based on silicon dioxide. Elastic and strength properties of composite materials are explored, connected with peculiarities of the formation of structure and composition of coatings at plasma spraying, based on the proposed calculation–experimental technique, as well as with using results of measurements of internal friction and testing of compositions for the three–point bend. The work presents results of evaluation of the parameters of crack resistance and character of destruction of composite materials, based on examination of energy balance of the system "base – plasma coating" at the moment of crack initiation at exfoliation and cracking of coatings. We obtained values of intensity of stresses K1c of different systems and for the appropriate regions – in the grain body, on the border between the particles, in the area of interphase zone. The parameters of crack resistance (G1c, K1c) are calculated of the coating itself at its exfoliation and / or destruction. We applied the corresponding techniques for determining cohesive strength for some cases of the crack propagation in the coating of dispersed structure depending on the composition of coating and ratio of modules of elasticity of the components of the given composition. The parameters of crack resistance are compared to physical and mechanical characteristics of plasma coatings – their adhesive and cohesive strength. The values of intensity of the released energy and coefficients of intensity of stresses at exfoliation or cracking are compared to such properties as adhesive and cohesive strength of the considered coatings.